Implementation of Corporate Social Responsibility of PTPN V (Case Study of Pantai Raja Village, Perhentian Raja District, Kampar Regency) - Marwah, Siti; Wedayanti, Made Devi (Pencerah, 2024)
This study aims to analyze the implementation of the Corporate Social Responsibility (CSR) program of PTPN V in Pantai Raja Village, Perhentian Raja District, Kampar Regency, and identify the factors inhibiting its effectiveness. The research employs a qualitative approach, guided by the implementation theory, which includes six key indicators: standard policies and objectives, resources, characteristics of implementing agents, communication between organizations and implementing activities, social conditions, and attitude disposition of implementers. Data were collected through interviews, observations, and documentation and analyzed descriptively. The findings reveal that the implementation of CSR regulations in Pantai Raja Village is hindered by several factors, including the absence of the CSR Forum's role in program execution, limited communication between the company and local government, lack of transparency regarding the company's capacity to implement CSR programs, and insufficient coordination between stakeholders. Furthermore, weak communication and collaboration between the company, government, and local communities exacerbate the issue. Based on these findings, the study concludes that the CSR implementation by PTPN V in Pantai Raja Village is categorized as underperformed. Enhanced communication, transparency, and stakeholder collaboration are recommended to improve CSR program execution and achieve its developmental objectives effectively.